2012
DOI: 10.4236/ajac.2012.37065
|View full text |Cite
|
Sign up to set email alerts
|

Contamination of Heavy Metals (Lead, Zinc, Magnesium and Manganese) Concentrations in Human Eyes

Abstract: The aim of our study is to measure the concentration of lead, zinc, magnesium and manganese, toxic/transition metals in human lens. The analyzed samples were categorized according to their personal habits (smoking, food, drinking and medical history). Demographic and laboratory characteristics of patients, the patients were twenty six males and twenty females. The comparison of trace elements between patients and control revealed significant increase of lead and manganese levels in patients and significant dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…As shown in Table 1 , none of the other studies analysed samples from the UK population. Environmental differences in Cd, Cr, Fe, Mg (that we did not analyse), Mn, Pb and Zn have previously been observed between individuals living in rural and urban environments within the same country [ 33 , 34 ], however we did not have access to this donor information.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Table 1 , none of the other studies analysed samples from the UK population. Environmental differences in Cd, Cr, Fe, Mg (that we did not analyse), Mn, Pb and Zn have previously been observed between individuals living in rural and urban environments within the same country [ 33 , 34 ], however we did not have access to this donor information.…”
Section: Discussionmentioning
confidence: 99%
“…The levels of metal ions in human lenses with cataract (i.e. removed during cataract surgery) has been more extensively investigated [ 18 , 21 34 ] (see Table 1 ), but these have not distinguished between disease-related and age-related changes.…”
Section: Introductionmentioning
confidence: 99%
“…Smokers had a mean age of cataract less than the non-smokers. Nazar S. Haddad et al [99], also found 50% higher level of lead in smoker's lens (1.5 µg/g of lens) as compared to non-smokers (1µg/g of lens). I found much higher level of lead (2.74 µg/g) in smokers than non-smokers (0.65 µg/g).…”
Section: Discussionmentioning
confidence: 88%
“…Exposure to Cu due to the daily instillation of eye drops, whose values ranged from 0.001 µg/day (eye drops 11 and 14 with preservatives, and 16 and 19 without preservatives) to 0.007 µg/day (eye drops 1, 8 and 9 with preservatives), were below the PDE for elemental impurities defined by the ICH Q3D guideline (R2) in the parenteral route (300 µg/day) ( Table 3 ). Cu plays a key role in the biochemistry of the human nervous system [ 67 ], being important for healing and slowing cataract growth [ 68 ]. On the other hand, intraocular foreign bodies containing Cu can cause inflammation, damage to the cell membranes and mitochondria in the retina [ 14 ], aseptic abscesses, cataracts, vitreous liquefaction and retraction, retinal damage and detachment, ocular hypotension [ 69 ], and corneal opacities [ 70 ].…”
Section: Discussionmentioning
confidence: 99%